A permanência de docentes de universidade pública no trabalho após o direito à aposentadoria: um estudo no Brasil e em Portugal - CABRAL, Maria da Conceição Rosa (Universidade Federal do Pará, 2019)
The present study aims to investigate the reasons for the permanence and working conditions of higher education teachers (professors) - linked to two educational institutions: Universidade Federal do Pará [Federal University of Pará] (UFPA) and Universidade de Lisboa [University of Lisbon] (ULisboa) - who remain in work activity after achieving the right to retirement. With regard to the aims, the study relates the reforms in the social security legislation and the postponement of public professors’ retirement in Brazil; identifies the reasons for the professors’ permanence at work; and, also, investigates their work conditions and the potential situations of intensification of such work in the final phase of their career. In order to reach the proposed aims, the methodological path that is inscribed in a qualitative approach, adopted four procedures: i) an incursion into the Brazilian and Portuguese bibliographical production, in the sense of making a descriptive synthesis of qualitative research carried out on the theme "teaching work in higher education and retirement"; ii) an analysis of documents that summarize the social security legislation related to the retirement of higher education teachers in Brazil and Portugal; iii) an empirical research, using interviews with UFPA and ULisboa professors; iv) a survey of secondary data on retirement processes. The results of the study showed the relationship between the rules of social security and the permanence of higher education teachers in Brazil, since the security reforms sentenced the public employees the prolongation of the time of permanence in the work and postponement of retirement. Regarding permanence, the study points out that the recognition of work; vitality and health; pleasure and satisfaction; and, also, identification and belonging stood out among the cited reasons. The retired women justify their stay, also, for enjoying more free time and freedom in their teaching work. Both at UFPA as at ULisboa, themes such as vitality and health of subjects, plasure and satisfaction, participation, contribution and cooperation, as well as the financial incentive have been identified as common reasons for the permanence of teachers at their universities. With regard to working conditions, the study showed that professors of both universities, during the last phase of their career, undergo the changes of the world of work, such as the reconfiguration of this work by the new ways of organizing the production process, which causes these professors go through intensified working conditions. From the triangulation of narratives, legal documents and literature review, the study concludes that the reasons for the permanence of higher education teachers at work result from a combination of elements, and that work is so central in the lives of these people that, even in intensified conditions, some intend to remain working until compulsory retirement and few evaluate the possibility of building other meanings for life outside the world of work.